Mitochondrial DNA diversity and genetic structure of striped dolphin Stenella coeruleoalba in the Northern Ionian Sea - Antonacci, Rachele; Linguiti, Giovanna; Paradiso, Federica; Scalone, Chiara; Fanizza, Carmelo; Ciani, Elena; Cipriano, Giulia; Ciccarese, Salvatrice; Carlucci, Roberto (Frontiers in Marine Science, 2023)
In the framework of global and EU policies focused on stopping the loss of biodiversity process, deepening the genetic variability, especially of populations species identified as threatened, is crucial for defining conservation units and developing appropriate conservation strategies. This is more urgent for cetacean species in the Mediterranean because they assume a key ecological role in the marine food web and are severely affected by numerous and different anthropogenic pressures. This study aims to increase information on the genetic variability of striped dolphin in the Northern Ionian Sea by investigating the population structure, phylogenetic relationships and phylogeographic patterns using two mtDNA markers. From October 2020 to August 2021, a total of 88 skin tissue samples were collected from free-ranging dolphins in the Gulf of Taranto by applying the non-invasive technique of skin swabbing. An acceptable amount of DNA was extracted from 86 samples and used for subsequent genetic analysis conducted on the partial sequences of 421 and 704 bp in length of the cytb gene and D-loop control region, respectively. In addition, the sequences of the two mtDNA markers were joined together to compose a mtDNA concatenated sequence of 1125 bp for each sampled dolphin in order to investigate the genetic variability of the species population in the study area. Genetic analysis highlighted a low nucleotide diversity and high haplotypic diversity of the striped dolphin of the Gulf of Taranto, suggesting a population in rapid expansion after a period of reduction in size and diversity of the initial population. The phylogenetic analyses revealed the presence of at least two different lineages of Stenella coeruleoalba in the Mediterranean Sea, one specific to the Northern Ionian Sea and one shared with the Mediterranean population, confirming results already obtained for the local unit in the Gulf of Taranto. The results point out a potential problem of hybridization between striped and common dolphins which needs to be further investigated. Therefore, increasing the analysis of several markers may increase understanding of the genetic diversity of the population in the Ionian Sea and represent a useful tool to support the implementation of future effective conservation measures.